The Future Classroom Teaching Research of Packaging Design Course - Feng, Lei (Transactions on Economics, Business and Management Research, 2023)
Driven by the improvement of teaching innovation ability, the construction of teacher-student growth community and the improvement of college talent training quality will completely change the current situation of students not listening in class, and there will be any new requirements in the future, which urge us to constantly carry out curriculum reform.But our development goal is for the future.This teaching reform can improve the state of students listening to lectures, is an effective curriculum reform.